Long-term monitoring study of beached seabirds shows that chronic oil pollution in the southern North Sea has almost halted. (15th February 2017) - Stienen, Eric W.M.; Courtens, Wouter; Van de walle, Marc; Vanermen, Nicolas; Verstraete, Hilbran
Abstract: Trends in oil rates of beached seabirds reflect temporal and spatial patterns in chronic oil pollution at sea. We analysed a long-term dataset of systematic beached bird surveys along the Belgian North Sea coast during 1962–2015, where extreme high oil contamination rates and consequently high mortality rates of seabirds during the 1960s used to coincide with intensive ship traffic. In the 1960s, > 90% of all swimming seabirds that washed ashore were contaminated with oil and estimated oil-induced mortality of seabirds was probably several times higher than natural mortality. More than 50 years later oil rates of seabirds have dropped to historically low levels while shipping is still very intense, indicating that chronic oil pollution has significantly declined. The declining trend is discussed in the light of a series of legislative measures that were enacted in the North Sea region to reduce oil pollution. Highlights: One of the longest studies on beached seabirds Seabird mortality due to oil pollution amounted to several times natural mortality. At present chronic oil pollution in the southern North Sea has almost halted. Suggestion that legislative measures to reduce oil rates were effective. Logistic regression approach should be used to analyse trends in oil rate.